Secure or fearful, who will be more resentful? Investigating the interaction between regulatory focus and attachment style. Issue 5 (19th August 2019) - Kordrostami, Melika; Kordrostami, Elika
Abstract : Purpose: This study aims to examine the impact of consumers' individual differences on their reactions to brand failure. Design/methodology/approach: Three studies (one qualitative, one survey and one experiment) were conducted. Study 1 aimed to understand consumers' thoughts at the time of brand failure. Studies 2 and 3 investigated the impact of regulatory focus and its interaction with consumers' attachment style on their reactions to brand failure. Findings: This research establishes that consumers demonstrate different types of behaviors at the time of brand failure. Specifically, those with a promotion focus display less negative (revenge and brand avoidance) and more positive (trust and loyalty) behavior than those with a prevention focus. Furthermore, this research shows an interaction between consumers' attachment style and regulatory focus. The impact of regulatory focus holds only for secure consumers; for fearful consumers, regulatory focus does not change their behavior. Research limitations/implications: The study reveals the impact of regulatory focus and attachment styles on consumer behavior at the time of brand failure. Future research might examine the impact of these factors over time, rather than only at the time of the incident. Practical implications: Marketers should be aware of the impact of attachment style and regulatory focus after a brand failure. This knowledge will enable them to customize their communication tools to trigger their desired condition. This research also emphasizes the role of customer service at the time of crisis. Originality/value: This research is the first to investigate the impact of regulatory focus and attachment style on consumers' reactions to brand failure.